KAMPUNG BAHARI NUSANTARA AS AN ALTERNATIVE FOR MULTI-SECTOR DEVELOPMENT OF A VILLAGE - Sriadi, Sriadi; Y.S., Victor Pardamean; Nurisnaeny, Poppy Setiawati (International Review of Humanities Studies, 2023)
Kampung Bahari Nusantara is a village that can serve as a form of unity between the Indonesian Army and the coastal communities to support the Indonesian Navy's task of developing maritime potential. Maritime potential development activities are carried out independently or with support from the government or non-ministerial government institutions, as well as other components of the nation, in order to realize the maritime defense power. These activities strengthen the maritime defense in facing threats, disturbances, obstacles, and challenges, including the development of sea dimension strength, and assists the government in preparing national potential by fostering demographic geography and social conditions. This research on the participation of the Lamongan Coastal Community was carried out using qualitative research methods with direct and indirect sources from various writings. This research utilizes a naturalistic method as it is carried out in a natural setting and is based on the experience research subjects.